Pengendara sebagai Faktor Risiko Terjadinya Kecelakaan Lalu Lintas Sepeda Motor Tahun 2010 - Sahabudin Hendro Wartatmo, Susy Kuschitawati (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Motor Riders as Risk Factor for the Incidence of Motor Cycle Traffic Accident Municipality 2010Background: Traffic accident (TA) has become a public health problem nowadays. Everyday more than 3,000 people die due to TA worldwide. As much as 80% of TA happens in low income countries and 90% in medium income countries annually causing disability-adjusted life years (DALYs). In 2020 it is estimated that TA will be in the third rank after cardiac ischemia and depression worldwide. Vehicles on the road in Yogyakarta Municipality have changed the transport mode from bicycle to motorcycle. Three factors that often because motorcycles TAare human, vehicle and road factors. More than 80% of TA rate is due to human factor. Within the past five years there has been an increase in motorcycle TA cases in Yogyakarta Municipality.Objective: The study aimed to identify exposure to risk factor associated with motorcycle TA in Yogyakarta Municipality.Method: The study was observational that used case control study design. Samples consisted of 266 people comprising 133 cases and 133 controls purposively taken. Cases were riders that had motorcycle TA in Yogyakarta. Data of cases were taken from Polwiltabes and hospitals in Yogyakarta Municipality, whereas data of the control group were obtained from relatives and or neighbours of the case group.Result: The result of multivariate analysis showed that there was association between use of mobile phone during the drive OR=2.24 (p=0.044), speed > 50 km/hour OR=1.974 (p=0.025) and ownership of driving license type C OR=1.956 (p=0.009) and the incidence of motorcycle TA.Conclusion: Use of mobile phone during driving, speed > 50 km/hour and non ownership of driving license type C were risk factors for the incidence of motorcycle TA in Yogyakarta Municipality.Keywords: driver, risk factors, traffic accident, motorcycle